PENERAPAN PDB MODEL DI MUSEUM SATWA JATIM PARK 2 MELALUI TAKSIDERMI - Rahma Santhi Zinaida; Idil Adha (Jurnal Komunikasi dan Budaya, 2021)
Tourism is an activity that directly touches and involves the community, thereby bringing various benefits to the local community and its surroundings. The efforts to develop a tourist destination must pay attention to various factors that affect a tourist destination. One of the areas in East Java which is known as a tourism city is Batu City. In marketing communication there are strategies that can make products different from competitors and even exceed them. Such as what was done by the Jatim Park 2 tourist spot which used a promotion differentiation strategy through the PDB model. The purpose of this study is to determine the promotion differentiation strategy through animal preservation in Jatim Park 2 through PDB theory. Promotional differentiation from Jatim Park is to display the uniqueness of the preserved animals found in the animal museum. Besides being a recreation area, Jatim Park 2 is also a means of education for visitors who come to Jatim Park 2